Kite-borne Spectroscopic Observations of the Corona During the 2023 April 20 Total Solar Eclipse - Benedikt Justen; Shadia Rifai Habbal; Matthias Justen; Oliver Mayer; Adalbert Ding; Klemens Brumann; Herbert Stehr (The Astrophysical Journal Letters)
We report in this Letter on the first use of a kite as an airborne platform for coronal observations during total solar eclipses, to mitigate the detrimental impact of clouds when present. In this first innovative attempt, the scientific payload was chosen to be a single-channel color spectrometer operating in high order over the wavelength range of 400–1000 nm, with light being fed from a coelostat that tracked the Sun optically. The payload was made airborne by a Cody-box-type kite with a wingspan of 6.5 m and launched from Cape Range National Park in North West Australia during the 2023 April 20 total solar eclipse. The kite and payload reached a terminal altitude of 450 m about 30 minutes prior to second contact and remained airborne 1 hr past the 58 s of totality. Although the tracking was not perfect, it nevertheless enabled the acquisition of two coronal spectra. This first successful technology demonstration paves the way for the feasibility of future low-cost kite-borne payloads for astronomical observations not limited to total solar eclipses.